2003 International Symposium on Compound Semiconductors
DOI: 10.1109/iscs.2003.1239963
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication processes for high performance InAs-based HBTs

Abstract: The potential for InAs-based heterojunction bipolar transistors (HBTs) to be used for high speed, low power applications has been demonstrated.[l] The material properties that give InAs an advantage over InGaAs-based HBTs include a low bandgap, low electron effective mass, high peak velocity and high electron mobility. However, a new technology presents new challenges for process development engineers. In this talk, InAs-based HBT technology will be discussed. Several of the available fabrication processes wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…InAs-based transistors are promising for applications requiring high-speed, low-power integrated circuits. 1,2 The use of strained alloys close in composition to InAs, such as Al x In 1−x As and InAs y P 1−y , adds further flexibility to the design of these devices. 3 Since the base layers of InAs-based heterojunction bipolar transistors are usually less than 50 nm, 3 shallow and thermally stable ohmic contacts are a critical factor for reliable high-speed devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…InAs-based transistors are promising for applications requiring high-speed, low-power integrated circuits. 1,2 The use of strained alloys close in composition to InAs, such as Al x In 1−x As and InAs y P 1−y , adds further flexibility to the design of these devices. 3 Since the base layers of InAs-based heterojunction bipolar transistors are usually less than 50 nm, 3 shallow and thermally stable ohmic contacts are a critical factor for reliable high-speed devices.…”
mentioning
confidence: 99%
“…The compositions of InAs y P 1−y of interest have y near 1, making past work on contacts to InAs of particular interest. Katz et al reported a specific contact resistance of 1 ϫ 10 −7 ⍀ cm 2 for Ti/Pt ͑50:60 nm͒ contacts annealed at 450°C for 30 s on p-InAs with a doping level of 1 ϫ 10 19 cm −3 , but mixing of Ti and InAs was observed by Auger electron spectroscopy ͑AES͒ in the samples annealed for 30 s at a temperature of 400°C. 4 Lysczek et al compared Pd/Pt/Au ͑3:50:145 nm͒ and Ti/Pt/Au ͑50:60:145 nm͒ contacts on the same p-InAs epi layer, and they found that the contacts with Pd as the first contact layer provided lower specific contact resistances than Ti-based contacts.…”
mentioning
confidence: 99%
“…The high mobility, high peak velocity, and low contact resistance and low bandgap of InAs, coupled with a large conduction band offset to AlSb, has allowed demonstration of high speed, low power HIEMT devices [1,2] and low Vbe, high speed DHBT devices [3,4]. Recent work has shown that circuits produced in these emerging device technologies exhibit high speed performance, as well as low DC power consumption [4][5][6][7][8], suggesting that these circuit technologies can play a critical role in the severely power-constrained environments of space-based systems.…”
Section: Introductionmentioning
confidence: 99%